Hubungan Literasi Digital dalam Pemanfaatan Kecerdasan Buatan Terhadap Motivasi Belajar Mahasiswa - Elinda Yuniati; Yani Setiani; Aan Hendrayana (Paedagogie, 2026)
Students' ability to utilize artificial intelligence (AI) critically and productively in learning is largely determined by the quality of their digital literacy. This study aims to analyze the strength of the relationship between digital literacy in the use of AI and students' learning motivation, uncover the meaning students give to this relationship, and identify the reinforcing and inhibiting factors underlying it. The design used is a quantitative study with a correlational design. The questionnaire instrument is based on a Likert Scale that has been tested for validity and reliability. Because the data did not meet the assumption of normality (Kolmogorov-Smirnov Sig. = 0.005), hypothesis testing used Spearman Rank correlation. The results showed a significant positive relationship (r = 0.479; p = 0.000) with a coefficient of determination R² = 0.181, meaning that digital literacy in the use of AI contributes 18.1% to learning motivation. Descriptively, 93.2% of students are classified as high–very high digital literacy, and 95.9% have high–very high learning motivation. These findings underscore the urgency of explicitly integrating AI digital literacy training into the mathematics education curriculum.